Evaluation of the systemic effect of bone formation marker released by endodontic calcium silicate-based sealers in local tissues, the bloodstream, and body organs - De Azevedo Queiroz, Índia Olinta; de Mello, Wagner Garcez [UNESP]; Machado, Thiago [UNESP]; de Oliveira, Maria Carolina Guiotti; Vasconcelos, Bruno Carvalho; de Oliveira, Sandra Helena Penha [UNESP]; Duarte, Marco Antonio Hungaro (Springer Nature, 2025)
Calcium silicate-based sealers are bioactive materials that release ions when in contact with body fluids. Therefore, this study aims mapping/trace bone formation markers released by MTA Fillapex, BioRoot RCS, and experimental tricalcium silicate-based sealer (CEO) into subcutaneous tissues, bloodstream and body organs. Toward, polyethylene tubes filled with sealers were implanted into connective tissue of Wistar rats. On days 7, 15, 30, and 45 after implantation, blood samples were collected to measure calcium (Ca2+), phosphorus (P), and alkaline phosphatase (ALP) levels. Thereafter, the animals were killed, and the brain, liver, kidneys, and subcutaneous tissue were removed and processed to determine the concentrations of Ca2+ and P by ICP-OES. Similar Ca2+ levels were observed in subcutaneous tissue for all groups, although, at 45 days, it was identified a reduction in Ca2+ serum levels of CEO compared to those two other sealers and an increase in Ca2+ levels in the liver compared to those released by MTA Fillapex. In contrast, no trace of P was detected in any tissue; moreover, plasma P and ALP serum levels of MTA Fillapex were higher at day 30. Our findings showed that Ca2+ were identified in local tissues, bloodstream, and organs from all sealers. The up-regulation of bone marker levels promoted by sealers can modify body homeostasis and induce tissue damage. Besides, MTA Fillapex was associated with a raise of bone marker levels, suggesting a possible systemic effect. The sealer composition can affect not only the local repair process but also the systemic health.
Keywords: Body organs; Bone markers; Calcium silicate; Root canal filling